2020
DOI: 10.3390/medicina56100495
|View full text |Cite
|
Sign up to set email alerts
|

Post-Delivery Milking Delay Influence on the Effect of Oral Supplementation with Bovine Colostrum as Measured with Intestinal Permeability Test

Abstract: Background and objective: The health supplement bovine colostrum reportedly improves immunity and regulates intestinal homeostasis. Reliable assessment methods are needed to ensure the satisfactory biological activity of all marketed colostrum products. Of the well-established effects of colostrum use, the restoration of appropriate intestinal permeability assessed with the lactulose/mannitol (L/M) differential sugar absorption test upon supplementation with colostrum has been consistently observed. Milking ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In parallel with the fall off in IgG and growth factor content, studies examining the biological activity of BC collected on day 1 post-calving versus day 3 have demonstrated major differences in their ability to stimulate the growth and repair of human gut cells in in vitro models of gastric damage [ 83 ] and in reducing increased gut permeability in humans [ 129 ]. However, differences in the BC collection period are not the only cause of bioactive variability; variation in storage conditions, processing, and pasteurisation may also contribute to the six-fold difference in bioactivity seen when commercial products were compared [ 83 ].…”
Section: Assessment Of Bc For Human Usementioning
confidence: 99%
“…In parallel with the fall off in IgG and growth factor content, studies examining the biological activity of BC collected on day 1 post-calving versus day 3 have demonstrated major differences in their ability to stimulate the growth and repair of human gut cells in in vitro models of gastric damage [ 83 ] and in reducing increased gut permeability in humans [ 129 ]. However, differences in the BC collection period are not the only cause of bioactive variability; variation in storage conditions, processing, and pasteurisation may also contribute to the six-fold difference in bioactivity seen when commercial products were compared [ 83 ].…”
Section: Assessment Of Bc For Human Usementioning
confidence: 99%
“…Another reason for the difference in results may be a difference in the bioactive components in the bovine colostrum itself. Due to some inconsistent results between bovine colostrum studies, Halasa and colleagues investigated the impact of delayed milking post-partum on the ability of bovine colostrum to reduce permeability markers in recreational athletes [ 64 ]. They found that bovine colostrum obtained 72-hour post-partum was less effective than colostrum from 2- and 24-hours post-partum.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability or hyperpermeability is a recently observed medical disorder in which the tight connections in the gut epithelial wall lose their integrity, allowing material from the lumen to leak into the bloodstream or other organs [ 95 ]. Hałasa et al [ 96 ] conducted a placebo-controlled, double-blind trial on healthy individuals to determine the effectiveness of BC supplementation in responses to intestinal permeability, conducting a further assessment with the mannitol/lactulose differential sugar absorption test. For the study, the colostrum samples were collected at different lengths of time after parturition (2, 24, and 72 h).…”
Section: Current Evidence Of Therapeutic Use Of Bcmentioning
confidence: 99%